2018
DOI: 10.2337/dc18-1032
|View full text |Cite
|
Sign up to set email alerts
|

First Genome-Wide Association Study of Latent Autoimmune Diabetes in Adults Reveals Novel Insights Linking Immune and Metabolic Diabetes

Abstract: OBJECTIVELatent autoimmune diabetes in adults (LADA) shares clinical features with both type 1 and type 2 diabetes; however, there is ongoing debate regarding the precise definition of LADA. Understanding its genetic basis is one potential strategy to gain insight into appropriate classification of this diabetes subtype.RESEARCH DESIGN AND METHODSWe performed the first genome-wide association study of LADA in case subjects of European ancestry versus population control subjects (n = 2,634 vs. 5,947) and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 41 publications
5
108
1
Order By: Relevance
“…The overlap of transcriptomes of human islets exposed to cytokines and islets isolated from humans with recent-onset type 1 diabetes supports a primary role of cytokines in mediating beta cell dysfunction and loss in type 1 diabetes [10][11][12]. A recent genome-wide association study of adult-onset type 1 diabetes reported linkage to one of the major targets of HIF1α signalling, PFKFB3 [36]. As yet, it is unknown if this linkage is to variants of PFKFB3 that have increased or decreased activity.…”
Section: Discussionmentioning
confidence: 76%
“…The overlap of transcriptomes of human islets exposed to cytokines and islets isolated from humans with recent-onset type 1 diabetes supports a primary role of cytokines in mediating beta cell dysfunction and loss in type 1 diabetes [10][11][12]. A recent genome-wide association study of adult-onset type 1 diabetes reported linkage to one of the major targets of HIF1α signalling, PFKFB3 [36]. As yet, it is unknown if this linkage is to variants of PFKFB3 that have increased or decreased activity.…”
Section: Discussionmentioning
confidence: 76%
“…• Maturity-onset diabetes of youth (MODY), also called maturity-onset hyperglycemia of youth (MOHY) [14][15][16][17][18][19][20][21][22][23][24][25] • Flatbush diabetes [26][27][28] • Latent autoimmune diabetes in adults (LADA). [29][30][31][32][33][34] Each of these is discussed in more detail below ( Table 1). 8,10,11,[14][15][16][17][18][19][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The expectation that the results of the Human Genome Project 35,36 would provide greater refi nement i...…”
Section: ■ Types and Biomarkers Of Diabetesmentioning
confidence: 99%
“…[29][30][31][32][33][34] Each of these is discussed in more detail below ( Table 1). 8,10,11,[14][15][16][17][18][19][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The expectation that the results of the Human Genome Project 35,36 would provide greater refi nement in classifying type 2 diabetes and guiding glucose-lowering regimens has not yet been fully realized. 37 Dozens of genetic markers are now associated with type 2 diabetes, and many are associated with phenotypic and mechanistic components of the pathophysiology of diabetes, including insulin secretion, insulin resistance, and obesity.…”
Section: ■ Types and Biomarkers Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of the type 1 diabetes MHC locus and the type 2 diabetes TCF7L2 locus have suggested that LADA sits at the "genetic meeting point" of these two traits (44,45). Indeed, one study suggested that the TCF7L2 locus could be used in young patients to distinguish autoimmune from nonautoimmune causes of diabetes; however, it was not applicable to older patients (46).…”
Section: Tcf7l2 Latent Autoimmune Diabetes In Adults and Type 1 Diamentioning
confidence: 99%